Understanding sentiment shifts in central bank digital currencies - Conlon, T.; Corbet, S.; Hou, Y.; Hu, Y.; Larkin, C.; Oxley, Leslie (2024)
This paper investigates the motivations behind Central Banks’ issuance of digital currencies (CBDC) and the associated risks, including potential misuse and distrust from international actors. Non-issuance of CBDC could hinder financial innovation, while issuance might introduce risks related to cybercriminality and misuse by rogue nations. This study balances these motives by assessing whether sentiment provides significant insights for policymakers and regulators. Utilising social media data, we analyse the impact of CBDC-related central bank releases, severe negative events, and contagion effects from traditional financial markets on CBDC sentiment. Our findings reveal that central bank announcements generally boost positive sentiment towards CBDCs through the provision of reassurance, whereas major geopolitical events trigger significant fluctuations in sentiment. The research highlights the critical role of sentiment analysis in understanding external influences on the development and implementation of CBDCs.